Kriteria Memilih Pasangan Hidup Dalam Al-Qur’an - Heri Khoiruddin (STAI Siliwangi Bandung, 2016)
Through the Qur'an, Islam guides people who want to establish a relationship of love through marriage, by giving some criteria and signs that should be considered for those who want to choose a spouse. These criteria are important because the fulfillment of these criteria will be the guarantee of the happening of a happy marriage not only in the world but also in the afterlife. This paper aims to explain how the husband and wife are described by the Qur'an and what are the criteria that should be considered the recommendations of the Qur'an. With the presentation of these criteria, this paper is expected to contribute to the implementation of family life and harmonious society, not only for the present but also future generations of life.